The The Relationship Between Stress Levels, Sports Achievement and Academic Achievement in Sports Athletes Indoor and Outdoor Universitas Negeri Semarang - Ettania Agustina; Heny Setyawati; Donny Wira Yudha Kusuma (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Stressor in athletes are categorized into three: competitive, organizational, personal. The cause of stress can be caused by the location of the room, the classification of sports based on the place of space is divided into two: indoor and outdoor. In sports psychology, stress levels affect sports and academic achievement. The purpose of this study was to analyze differences in stress levels, relationship between stress levels and sports achievements, and the academic achievements of UNNES athletes. This study used a quantitative approach with the help of the DASS 42 questionnaire. Data analysis was done using the T-test, correlation and regression. The results of the study showed the mean stress level in athletes indoor 1.86 athletes outdoor 1.50 statistically it is known that there are differences in the mean stress levels of athletes indoor and outdoor. Based on value Sig. 0.471>0.05, which means there is no relationship between stress levels and sports achievements. Other results show value Sig. between the level or category of stress and academic achievement is 0.652>0.05, meaning that there is no relationship between the stress level variable and the athlete's academic achievement variable at Universitas Negeri Semarang. However, the effective contribution that influences it is 1.2%.